FTO plays a crucial role in gastrointestinal cancer and may be a target for immunotherapy: an updated review - Ren, Xiangqing; Tang, Xiaolong; Huang, Tian; Hu, Zenan; Wang, Yuping; Zhou, Yongning (Frontiers in Oncology, 2023)
Gastrointestinal cancer is a common malignancy with high mortality and poor prognosis. Therefore, developing novel effective markers and therapeutic targets for gastrointestinal cancer is currently a challenging and popular topic in oncology research. Accumulating studies have reported that N6-methyladenosine is the most abundant epigenetic modification in eukaryotes. N6-methyladenosine plays an essential role in regulating RNA expression and metabolism, including splicing, translation, stability, decay, and transport. FTO, the earliest demethylase discovered to maintain the balance of N6-adenosine methylation, is abnormally expressed in many tumors. In this review, we discuss the molecular structure and substrate selectivity of FTO. we focus on the role of FTO in gastrointestinal tumor proliferation, migration, invasion, apoptosis, autophagy, immune microenvironment, and its molecular mechanisms. We also discuss its potential in the treatment of gastrointestinal cancers.